Dendritic‐Like Molecules Built on a Pillar[5]arene Core as Hole Transporting Materials for Perovskite Solar Cells. Issue 31 (19th May 2021) - Bettucci, Ottavia; Pascual, Jorge; Turren‐Cruz, Silver‐Hamill; Cabrera‐Espinoza, Andrea; Matsuda, Wakana; Völker, Sebastian F.; Köbler, Hans; Nierengarten, Iwona; Reginato, Gianna; Collavini, Silvia; Seki, Shu; Nierengarten, Jean‐François; et al.
Abstract: Invited for the cover of this issue are the groups of S. Seki (Kyoto), G. Reginato (Sesto Fiorentino), J.‐F. Nierengarten (Strasbourg), A. Abate (Berlin) and J. L. Delgado (San Sebastian). The image depicts an artistic view of a dendrimer‐like hole transporting material at work in a perovskite solar cell. Read the full text of the article at 10.1002/chem.202101110 . Abstract : " The preparation of novel hole transporting materials able to compete with the reference spiro‐OMeTAD, has been a hot topic in photovoltaics in the last years. In the present paper, we have proposed a new design principle for the preparation of hole transporting materials for perovskite solar cells. Our approach relies on the functionalization of a clickable pillar[5]arene core with peripheral triarylamines to generate dendrimer‐like structures ." Read more about the story behind the cover in the Cover Profile and about the research itself on page 8110 ff. (DOI: 10.1002/chem.202101110 ).